If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -1) + 2(x + 2) = (3x + 3) + (x + 6) + (3x + 3) Reorder the terms: 2(-1 + 3x) + 2(x + 2) = (3x + 3) + (x + 6) + (3x + 3) (-1 * 2 + 3x * 2) + 2(x + 2) = (3x + 3) + (x + 6) + (3x + 3) (-2 + 6x) + 2(x + 2) = (3x + 3) + (x + 6) + (3x + 3) Reorder the terms: -2 + 6x + 2(2 + x) = (3x + 3) + (x + 6) + (3x + 3) -2 + 6x + (2 * 2 + x * 2) = (3x + 3) + (x + 6) + (3x + 3) -2 + 6x + (4 + 2x) = (3x + 3) + (x + 6) + (3x + 3) Reorder the terms: -2 + 4 + 6x + 2x = (3x + 3) + (x + 6) + (3x + 3) Combine like terms: -2 + 4 = 2 2 + 6x + 2x = (3x + 3) + (x + 6) + (3x + 3) Combine like terms: 6x + 2x = 8x 2 + 8x = (3x + 3) + (x + 6) + (3x + 3) Reorder the terms: 2 + 8x = (3 + 3x) + (x + 6) + (3x + 3) Remove parenthesis around (3 + 3x) 2 + 8x = 3 + 3x + (x + 6) + (3x + 3) Reorder the terms: 2 + 8x = 3 + 3x + (6 + x) + (3x + 3) Remove parenthesis around (6 + x) 2 + 8x = 3 + 3x + 6 + x + (3x + 3) Reorder the terms: 2 + 8x = 3 + 3x + 6 + x + (3 + 3x) Remove parenthesis around (3 + 3x) 2 + 8x = 3 + 3x + 6 + x + 3 + 3x Reorder the terms: 2 + 8x = 3 + 6 + 3 + 3x + x + 3x Combine like terms: 3 + 6 = 9 2 + 8x = 9 + 3 + 3x + x + 3x Combine like terms: 9 + 3 = 12 2 + 8x = 12 + 3x + x + 3x Combine like terms: 3x + x = 4x 2 + 8x = 12 + 4x + 3x Combine like terms: 4x + 3x = 7x 2 + 8x = 12 + 7x Solving 2 + 8x = 12 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 2 + 8x + -7x = 12 + 7x + -7x Combine like terms: 8x + -7x = 1x 2 + 1x = 12 + 7x + -7x Combine like terms: 7x + -7x = 0 2 + 1x = 12 + 0 2 + 1x = 12 Add '-2' to each side of the equation. 2 + -2 + 1x = 12 + -2 Combine like terms: 2 + -2 = 0 0 + 1x = 12 + -2 1x = 12 + -2 Combine like terms: 12 + -2 = 10 1x = 10 Divide each side by '1'. x = 10 Simplifying x = 10
| -2-7r+6r-9= | | x/5-16=19 | | e^5x+1=e^7 | | 5n+8-1n=6(1n-1) | | X*x*2=122 | | 3(2b-4)+6=2(3b-6) | | -(2x-5)-(2x-5)+4=6(x-1)-(2x+7)+3 | | 2x-1/x=4/3 | | 6(a+3)=9 | | 5x^2-37=43 | | 5x+7/3=2x+9 | | xy^3/y^5 | | x+15+x=x+45+x+40+x+25 | | (9n^6)^(1/2) | | 4=u+6 | | 40a^2+195+140=0 | | 8xy^3/6y^5 | | 4X-3=2-6X | | x^2-21x-216=0 | | (n+6)((n+6)-10)=200 | | -(7x-3)-(4x-5)+11=-3(x-1)-(11X+2)+3 | | 8x^204=28 | | (n^(-4/15))*(5n^(3/5)) | | 3/75=x/10 | | 6y+(3y+3)=16 | | n^-4/15*5n^3/5 | | -5m^2+245=0 | | ln(3x+1)+ln(x)=ln(2) | | 3(2y+3)=-3y-9 | | Y=-16x^2+384 | | 3n+5forn=4 | | 5x-1.2=9x-.8 |